Tracking global invasion pathways of the spongy moth (Lepidoptera: Erebidae) to the United States using stable isotopes as endogenous biomarkers. Issue 7 (13th July 2022) - Freistetter, Nadine‐Cyra; Simmons, Gregory S.; Wu, Yunke; Finger, David C.; Hood‐Nowotny, Rebecca
Abstract: The spread of invasive insect species causes enormous ecological damage and economic losses worldwide. A reliable method that tracks back an invaded insect's origin would be of great use to entomologists, phytopathologists, and pest managers. The spongy moth ( Lymantria dispar, Linnaeus 1758) is a persistent invasive pest in the Northeastern United States and periodically causes major defoliations in temperate forests. We analyzed field‐captured (Europe, Asia, United States) and laboratory‐reared L. dispar specimens for their natal isotopic hydrogen and nitrogen signatures imprinted in their biological tissues (δ 2 H and δ 15 N) and compared these values to the long‐term mean δ 2 H of regional precipitation (Global Network of Isotopes in Precipitation) and δ 15 N of regional plants at the capture site. We established the percentage of hydrogen–deuterium exchange for L. dispar tissue (Pex  = 8.2%) using the comparative equilibration method and two‐source mixing models, which allowed the extraction of the moth's natal δ 2 H value. We confirmed that the natal δ 2 H and δ 15 N values of our specimens are related to the environmental signatures at their geographic origins. With our regression models, we were able to isolate potentially invasive individuals and give estimations of their geographic origin. To enable the application of these methods on eggs, we established an egg‐to‐adult fraction factor for L. dispar (Δegg‐adult = 16.3 ± 4.3‰). Our models suggested that around 25% of the field‐captured spongy moths worldwide were not native in the investigated capture sites. East Asia was the most frequently identified location of probable origin. Furthermore, our data suggested that eggs found on cargo ships in the United States harbors in Alaska, California, and Louisiana most probably originated from Asian L. dispar in East Russia. These findings show that stable isotope biomarkers give a unique insight into invasive insect species pathways, and thus, can be an effective tool to monitor the spread of insect pest epidemics. Abstract : To help slow the spread of invasive insects that cause ecological and economic burdens worldwide, we investigated a reliable method to track back an invaded insect's natal origin. We confirmed that the natal isotopic values of spongy moths were related to the environmental signatures at their geographic origins. Through regression analysis, estimations of the geographic origin of potentially invasive individuals were possible.